Respuesta :
C.
You can factor that equation to the following:
x(x - 3)(x + 2)
Then set each part equal to zero and solve individually.
You can factor that equation to the following:
x(x - 3)(x + 2)
Then set each part equal to zero and solve individually.
Answer with Step-by-step explanation:
We have to find the zeros of the function:
f(x)=x³-x²-6x
i.e we have to find the values of x such that:
x³-x²-6x=0
⇒ x(x²-x-6)=0
⇒ x(x²-3x+2x-6)=0
⇒ x(x(x-3)+2(x-3))=0
⇒ x(x+2)(x-3)=0
⇒ x=0 , x= -2 and x=3
Hence, Zeros of f(x)=x³-x²-6x are:
C. −2 , 0, and 3